Analisis Algoritma Genetika Tanpa Operasi Crossover Pada Kasus Travelling Salesman Problem Dengan Metode 2 Tahap Mutasi - Sean Coonery Sumarta (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2015)
The TSP problem can resolved using Genetic Algorithms. In other previous research, crossover is one process that can be eliminated from the genetic algorithm to get betternoptimization. This research tried to solve TSP by using genetic algorithms without using the crossover. To improve optimization by applying the method of mutation with 2 phases. Mutation operator used the inversion mutation, exchange mutation, and insertion mutation. The results using these methods is the average error percentage of optimum distance <10%.